Air combat from World War I to the present day - Newdick, Thomas (Amber Books, 2016)
Illustrated with action photographs and full-colour artworks, the chronologically ordered chapters outline the developments and landmarks in aerial combat through the decades, focusing on campaigns including the Spanish Civil War, the Blitzkrieg which began World War II, the Vietnam War, and the Falklands conflict. The book ends with an analysis of the use of U.S. and allied air power to fight insurgents in Iraq and Afghanistan